A molecular model for the differential activation of STAT3 and STAT6 by the herpesviral oncoprotein tip - Mazumder, Eman Dey; Jardin, Christophe; Vogel, Benjamin; Heck, Elke; Scholz, Brigitte; Lengenfelder, Doris; Sticht, Heinrich; Enßer, Armin (PLoS ONE, 2012)
Constitutive STAT signaling provides growth promoting signals in many forms of malignancy. We performed molecular modeling and molecular dynamics studies of the interaction between the regulatory Src homology 2 (SH2) domains of STAT3 and 6 with phosphorylated peptides of the herpesviral oncoprotein Tip, which facilitates Src kinase mediated STAT-activation and T cell proliferation. The studies give insight into the ligand binding specificity of the STAT SH2 domains and provide the first model for the differential activation of STAT3 or STAT6 by two distinct regions of the viral Tip protein. The biological relevance of the modeled interactions was then confirmed by activation studies using corresponding recombinant oncoproteins, and finally by respective recombinant viruses. The functional data give experimental validation of the molecular dynamics study, and provide evidence for the involvement of STAT6 in the herpesvirus induced T cell proliferation.
EVALuna2:8146

Both plasmacytoid dendritic cells and monocytes stimulate natural killer cells early during human herpes simplex virus type 1 infections - Vogel, Karin; Thomann, Sabrina; Vogel, Benjamin; Schuster, Philipp; Schmidt, Barbara (Immunology, 2014)
Herpes simplex virus type 1 (HSV-1), a member of the herpes virus family, is characterized by a short replication cycle, high cytopathogenicity and distinct neurotropism. Primary infection and reactivation may cause severe diseases in immunocompetent and immunosuppressed individuals. This study investigated the role of human plasmacytoid dendritic cells (pDC) in the activation of natural killer (NK) cells for the control of herpesviral infections. Within peripheral blood mononuclear cells, UV-inactivated HSV-1 and CpG-A induced CD69 up-regulation on NK cells, whereas infectious HSV-1 was particularly active in inducing NK cell effector functions interferon-? (IFN-?) secretion and degranulation. The pDC-derived IFN-? significantly contributed to NK cell activation, as evident from neutralization and cell depletion experiments. In addition, monocyte-derived tumour necrosis factor-? (TNF-?) induced after exposure to infectious HSV-1 was found to stimulate IFN-? secretion. A minority of monocytes was shown to be non-productively infected in experiments using fluorescently labelled viruses and quantitative PCR analyses. HSV-1-exposed monocytes up-regulated classical HLA-ABC and non-classical HLA-E molecules at the cell surface in an IFN-?-dependent manner, whereas stress molecules MICA/B were not induced. Notably, depletion of monocytes reduced NK cell effector functions induced by infectious HSV-1 (P < 0.05). Altogether, our data suggest a model in which HSV-1-stimulated pDC and monocytes activate NK cells via secretion of IFN-? and TNF-?. In addition, infection of monocytes induces NK cell effector functions via TNF-?-dependent and TNF-?-independent mechanisms. Hence, pDC and monocytes, which are among the first cells infiltrating herpetic lesions, appear to have important bystander functions for NK cells to control these viral infections.
EVALuna2:8241

Efficient generation of human natural killer cell lines by viral transformation - Vogel, Benjamin; Tennert, K.; Full, Florian; Enßer, Armin (Leukemia, 2014)
EVALuna2:8207